ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PANGSA PENGELUARAN PANGAN RUMAH TANGGA PETANI DI KECAMATAN SURUH KABUPATEN SEMARANG - M. A. Rachmah; Mukson -; S. Marzuki (Jurnal Pangan dan Gizi, 2017)
The aim of research to determine the factors that affect household food expenditure share of farmers in subdistrict Suruh regency Semarang. The research was conducted from November to December 2016 in the District Suruh. The method used in the study was a survey method. The locationdetermination is done purposively based on the number of farmers the most. The sampling method is based on a certain percentage, as much as 3% of the total population of 70 respondents farmers.Analysis of the data using calculations of household food expenditure share and multiple linear regression. Percentage share of food expenditure <60% 75.7% 24.3% ie the remaining share of food expenditure ≥ 60%. Simultaneously regression analysis showed that the factors of income, dependents, education homemaker, nutritional knowledge, the price of the staple rice, animal protein consumption and dummy daily consumption of vegetable and animal protein very significant effect on the share ofhousehold spending (P <0.01 ).Keywords : the share of food expenditures, food security